Yeha, Äthiopien: Forschungen zu Migrationsprozessen am nördlichen Horn von Afrika - Gerlach, Iris (e-Forschungsberichte des DAI, 2023)
Wandering movements and trade relations are traditionally viewed as basic factors for the transfer of culture and knowledge, the development of human populations and the emergence of new socio-cultural systems. With the beginning of the Sabaean migration to the northern Horn of Africa in the early 1st millennium BC cultural contacts between Sabaean immigrants and the indigenous population evolved. The manner and degree in which these contacts affected the participating groups and the results of these contacts are issues that are being investigated by the Ethiopian-German cooperation project. Comparison with models of migrations pertaining to historical times reveals that certain frequent mechanisms and movements can be presupposed for Sabaean migrations too, such as the composition of the emigrating groups, the motives for migration and the multiphased duration of these processes.